Indicator framework for sustainable production planning and controlling - Maximilian Zarte; Agnes Pechmann; Isabel L. Nunes (International Journal of Sustainable Engineering, 2019)
Production facilities serve to transform raw materials into products, usually with the goal of achieving a designated output, in terms of quantity and quality, with the minimum of cost and labour. With the aid of production planning and controlling (PPC) systems, raw material inputs, and labour can be planned to achieve a determined output of products. In general, the role of environmental and social aspects is neglected in production planning processes. Because of the growing pressure from politics and customers, sustainable production of products is becoming more important. One possibility for supporting sustainable manufacturing is, to integrate sustainable aspects in the production planning process. This paper presents input and output information for current PPC systems and discusses the need for additional information necessary for sustainable PPC. For this approach, a text review of cooperate social responsibility (CSR) reporting indicators provided by the GRI was performed. Based on the text review, an input-output model has been developed for conventional and another one for sustainable PPC systems. Through the comparison of the two input-output models, challenges and requirements for sustainable PPC systems have been defined as a basis for future work and analyses.